Laminated iron for packaging and preparation method thereof
By incorporating nano-SiO2 and HTPB grafted silane into PET film for coated iron, the method enhances mechanical properties and adhesion, addressing poor mechanical issues in existing coated iron, resulting in a high-performance packaging material for food and beverage applications.
Patent Information
- Application Number
- CN202411236168.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2024-12-13
AI Technical Summary
Existing coated iron for packaging materials suffer from poor mechanical properties, including slow high-temperature crystallization, high injection molding temperature, long processing cycles, poor thermal conductivity, and poor notch impact strength, which affect their performance in applications like food and beverage packaging.
A method involving the addition of nano-SiO2 and HTPB grafted silane to PET film, followed by copolymerization and extrusion, to enhance adhesion and mechanical properties, utilizing functionalized SiO2 as an oxidant and nucleating agent, and introducing mercapto groups for improved bonding with the iron plate.
The resulting coated iron exhibits high bonding strength, excellent adhesion, corrosion resistance, and improved mechanical properties, allowing for direct hot-melt bonding without adhesives, and is suitable for high-end food and beverage packaging.
Smart Images

Figure BDA0005027778390000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal packaging materials, and particularly relates to a film-coated iron for packaging and a preparation method thereof. Background Art
[0002] Among various coated metals, coated iron has attracted much attention in the packaging industry. Coated iron can be seen in beverage, food and other packaging. Coated iron has high wear resistance and corrosion resistance, and has excellent appearance and moisture resistance. It solves the hidden danger of bisphenol A, melamine and other substances entering food, and has a very broad application prospect in the metal packaging industry.
[0003] Coated iron is usually made by laminating a polyester film with a thickness of about 15-40μm with a cold-rolled steel plate. The selection and development of the film is very important. The film must have good barrier properties to avoid corrosion to the metal plate, and it must have strong adhesion to the substrate to prevent it from falling off during the cooking process. In addition, it also requires good moisture and airtightness. PET (polyethylene terephthalate) is a polymer film with good performance. It has the advantages of good light transmittance, mechanical properties, barrier properties, chemical stability and heat resistance. However, in actual applications, it has defects such as slow high-temperature crystallization rate, high injection molding temperature, long processing and production cycle, poor thermal conductivity and poor notch impact strength. Therefore, an effective improvement method is needed to make the PET film and metal steel plate hot roll laminated to obtain coated iron with good mechanical properties. Summary of the invention
[0004] The object of the present invention is to provide a film-coated iron for packaging and a preparation method thereof, so as to solve the problem of poor mechanical properties of the film-coated iron in the background technology.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A method for preparing coated iron for packaging, comprising the following steps:
[0007] S1. Add nano-SiO2 to methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate at 60-80°C, mix well to obtain a suspension, then add sodium methoxide, stir under vacuum reflux at 90-110°C for 6-8h, and collect by filtration to obtain functionalized SiO2;
[0008] S2. Add hydroxy-terminated polybutadiene (HTPB) and γ-mercaptopropyltrimethoxysilane (KH590) to tetrahydrofuran (THF), stir and mix well, then add 2,2-dimethoxy-2-phenylacetophenone (DMPA), react under 200W UV light for 2-4h, and obtain HTPB grafted silane couple by rotary evaporation;
[0009] S3. Add HTPB grafted silane and functionalized Si O2 to PET, heat and melt to 220-240 ° C, stir the copolymerization reaction at a speed of 100-200 rpm for 1-3h, and then extrude and press into a PET film;
[0010] S4. Thermally compounding the PET film with the pre-treated iron plate to obtain an iron-coated film.
[0011] Furthermore, the weight ratio of nano-SiO2, methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and sodium methoxide in S1 is 1:10-20:0.5-2.
[0012] Furthermore, the weight ratio of terminal hydroxyl polybutadiene, γ-mercaptopropyltrimethoxysilane, tetrahydrofuran, and 2,2-dimethoxy-2-phenylacetophenone in S2 is 1.5:0.3-0.4:50:0.01.
[0013] Furthermore, the amount of HTPB grafted silane in S3 is 2-6% of the amount of PET.
[0014] Furthermore, the amount of functionalized SiO2 in S3 is 1-3% of the amount of PET.
[0015] Furthermore, the thickness of the PET film in S3 is 10-20 μm.
[0016] Furthermore, the pretreatment of the iron plate in S4 is specifically to immerse the iron plate in an ethanol solution for ultrasonic cleaning for 10-30 minutes to remove surface oil stains, and air-dry.
[0017] Furthermore, the iron plate in S4 includes tinplate and cold-rolled iron plate.
[0018] Furthermore, the PET is PET masterbatch.
[0019] Furthermore, the stirring speed is 100-300 rpm.
[0020] A film-coated iron for packaging is prepared by the above preparation method.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The present invention provides a coated iron for packaging and a preparation method thereof. The PET film is prepared by adding HTPB grafted silane and functionalized SiO2 to PET by copolymerization and extrusion. On the one hand, asymmetric monomers are introduced into the PET molecules to destroy the original structure and reduce the regularity of the molecular chain arrangement. HTPB grafted silane is used to introduce mercapto groups into PET, and the mercapto groups are used to adsorb to the iron plate to enhance the adhesion between the metal plate and the iron plate. On the other hand, functionalized SiO2 is introduced to act as an oxidant in the copolymerization reaction and as a nucleating agent, and is loaded into the cross-linked structure network of PET to enhance the mechanical properties of the coated iron.
[0023] 2. Since the surface of nano-SiO2 has a large number of hydroxyl groups, it reacts with 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate through an ester exchange method to give nano-SiO2 antioxidant properties; through a thiol click chemistry reaction, γ-mercaptopropyltrimethoxysilane is grafted onto terminal hydroxyl polybutadiene, and the functionalized SiO2 participates in the copolymerization of PET and HTPB grafted silane as an antioxidant. Since molecular chains are generated during the melt copolymerization of PET and HTPB grafted silane, greater external force is required during the deformation process of extrusion film formation, so the mechanical capacity of the film is gradually improved.
[0024] 3. The iron plate is heated to above the melting point of the polymer film through a preheating zone by roller coating. When the surface layer of the polymer film in contact with the steel substrate is partially melted, the molten polymer between the film and the substrate is fully flowed, spread, contacted, cooled and solidified at the interface by the coating roller until the film and the substrate are roller-compounded and further cooled and solidified. During the roller coating process, a three-layer structure of steel substrate-molten polymer-solid polymer film is formed at the contact interface between the substrate and the film. The present invention utilizes the preferential adsorption effect of mercapto groups with the iron plate, so that the irregular molecular chains are mostly arranged on the side close to the iron plate, reducing the crystallinity of the molten polymer layer, avoiding recrystallization during the cooling process, and ensuring that the PET film has better adhesion and ductility on the basis of the original mechanical strength.
[0025] 4. The coated iron prepared by the present invention does not require adhesive during production and can be directly hot-melt bonded, with extremely high bonding strength and excellent anti-peeling performance. In addition, it does not contain harmful substances, has good chemical stability, excellent sulfur resistance, corrosion resistance and scratch resistance, smooth appearance, smooth surface, excellent processing performance, deep drawing resistance, wear resistance, and is not easy to break during processing. It can be widely used in high-end and medium-end food cans, beverages, and wine packaging. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] A method for preparing coated iron for packaging, comprising the following steps:
[0028] S1. Add 1 part of nano-SiO2 to 10-20 parts of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate at 60-80°C, mix well to obtain a suspension, then add 0.5-2 parts of sodium methoxide, stir under vacuum reflux at 90-110°C for 6-8h, and collect by filtration to obtain functionalized SiO2;
[0029] S2. 1.5 parts of HTPB and 0.3-0.4 parts of KH590 were added to 50 parts of THF, stirred at a speed of 100-300 rpm to mix evenly, and then 0.01 parts of DMPA were added, and the reaction was carried out under 200W UV light conditions for 2-4h, and the HTPB grafted silane couple was obtained by rotary evaporation;
[0030] S3. Add HTPB grafted silane and functionalized Si O2 to the PET masterbatch, heat and melt to 220-240°C, stir the copolymerization reaction at a speed of 100-200rpm for 1-3h, and extrude and press into a PET film with a thickness of 10-20μm; the amount of HTPB grafted silane is 2-6% of the amount of PET; the amount of functionalized Si O2 is 1-3% of the amount of PET;
[0031] S4. Soak the iron plate in an ethanol solution and perform ultrasonic cleaning for 10-30 minutes to remove surface oil stains. After air drying, heat-compound the iron plate with a PET film to obtain an iron-coated film.
[0032] Example 1
[0033] A method for preparing coated iron for packaging, comprising the following steps:
[0034] S1. At 70°C, add 1 part of nano-SiO2 to 15 parts of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, mix well to obtain a suspension, then add 1 part of sodium methoxide, stir under vacuum reflux at 100°C for 7 hours, and collect by filtration to obtain functionalized SiO2;
[0035] S2. 1.5 parts of HTPB and 0.35 parts of KH590 were added to 50 parts of THF, stirred at 200 rpm and mixed evenly, and then 0.01 parts of DMPA were added, and the reaction was carried out under 200W UV light conditions for 3.5h, and the HTPB grafted silane was obtained by rotary evaporation;
[0036] S3. Add HTPB grafted silane and functionalized SiO2 to the PET masterbatch, heat and melt to 230°C, stir at 150rpm for copolymerization for 2h, and then extrude and press into a PET film with a thickness of 15μm; the amount of HTPB grafted silane is 4% of the amount of PET; the amount of functionalized SiO2 is 2% of the amount of PET;
[0037] S4. Soak the iron plate in an ethanol solution and ultrasonically clean it for 30 minutes to remove surface oil stains. After air drying, heat-compound it with a PET film at 230°C to obtain an iron-coated film.
[0038] Example 2
[0039] A method for preparing coated iron for packaging, comprising the following steps:
[0040] S1. At 70°C, add 1 part of nano-SiO2 to 10 parts of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, mix well to obtain a suspension, then add 0.5 parts of sodium methoxide, stir under vacuum reflux at 100°C for 7 hours, and collect by filtration to obtain functionalized SiO2;
[0041] S2. 1.5 parts of HTPB and 0.3 parts of KH590 were added to 50 parts of THF, stirred at a speed of 200 rpm to mix evenly, and then 0.01 parts of DMPA were added, and the reaction was carried out under 200W UV light conditions for 3.5h, and the HTPB grafted silane couple was obtained by rotary evaporation;
[0042] S3. Add HTPB grafted silane and functionalized SiO2 to the PET masterbatch, heat and melt to 230°C, stir at 150 rpm for copolymerization for 2 hours, and then extrude and press into a PET film with a thickness of 15 μm; the amount of HTPB grafted silane is 2% of the amount of PET; the amount of functionalized SiO2 is 1% of the amount of PET;
[0043] S4. Soak the iron plate in an ethanol solution and ultrasonically clean it for 30 minutes to remove surface oil stains. After air drying, heat-compound it with a PET film at 230°C to obtain an iron-coated film.
[0044] Example 3
[0045] A method for preparing coated iron for packaging, comprising the following steps:
[0046] S1. At 70°C, add 1 part of nano-SiO2 to 20 parts of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, mix well to obtain a suspension, then add 2 parts of sodium methoxide, stir under vacuum reflux at 100°C for 7 hours, and collect by filtration to obtain functionalized SiO2;
[0047] S2. 1.5 parts of HTPB and 0.4 parts of KH590 were added to 50 parts of THF, stirred at a speed of 200 rpm to mix evenly, and then 0.01 parts of DMPA were added, and the reaction was carried out under 200W UV light conditions for 3.5h, and the HTPB grafted silane couple was obtained by rotary evaporation;
[0048] S3. Add HTPB grafted silane and functionalized SiO2 to the PET masterbatch, heat and melt to 230°C, stir at 150rpm for copolymerization for 2h, and then extrude and press into a PET film with a thickness of 15μm; the amount of HTPB grafted silane is 6% of the amount of PET; the amount of functionalized SiO2 is 3% of the amount of PET;
[0049] S4. Soak the iron plate in an ethanol solution and ultrasonically clean it for 30 minutes to remove surface oil stains. After air drying, heat-compound it with a PET film at 230°C to obtain an iron-coated film.
[0050] Comparative Example 1
[0051] A method for preparing coated iron for packaging, comprising the following steps:
[0052] S1. At 70°C, add 1 part of nano-SiO2 to 15 parts of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, mix well to obtain a suspension, then add 1 part of sodium methoxide, stir under vacuum reflux at 100°C for 7 hours, and collect by filtration to obtain functionalized SiO2;
[0053] S2. Add HTPB and functionalized SiO2 to the PET masterbatch, heat and melt to 230°C, stir at 150 rpm for copolymerization for 2 hours, and then extrude and press into a PET film with a thickness of 15 μm; the amount of HTPB is 4% of the amount of PET; the amount of functionalized SiO2 is 2% of the amount of PET;
[0054] S3. Soak the iron plate in an ethanol solution and perform ultrasonic cleaning for 30 minutes to remove surface oil stains. After air drying, heat-compound the iron plate with a PET film at 230°C to obtain an iron-coated film.
[0055] Comparative Example 2
[0056] A method for preparing coated iron for packaging, comprising the following steps:
[0057] S1. 1.5 parts of HTPB and 0.35 parts of KH590 were added to 50 parts of THF, stirred at 200 rpm to mix evenly, and then 0.01 parts of DMPA were added, and the reaction was carried out under 200W UV light conditions for 3.5h, and the HTPB grafted silane couple was obtained by rotary evaporation;
[0058] S2. Add HTPB grafted silane and SiO2 to the PET masterbatch, heat and melt to 230°C, stir at 150rpm for copolymerization for 2h, and then extrude and press into a PET film with a thickness of 15μm; the amount of HTPB grafted silane is 4% of the amount of PET; the amount of SiO2 is 2% of the amount of PET;
[0059] S3. Soak the iron plate in an ethanol solution and perform ultrasonic cleaning for 30 minutes to remove surface oil stains. After air drying, heat-compound the iron plate with a PET film at 230°C to obtain an iron-coated film.
[0060] Comparative Example 3
[0061] S1. Add HTPB and SiO2 to the PET masterbatch, heat and melt to 230°C, stir at 150rpm for copolymerization for 2h, and then extrude and press into a PET film with a thickness of 15μm; the amount of HTPB is 4% of the amount of PET; the amount of SiO2 is 2% of the amount of PET;
[0062] S2. Soak the iron plate in an ethanol solution and ultrasonically clean it for 30 minutes to remove surface oil stains. After air drying, heat-compound it with a PET film at 230°C to obtain an iron-coated film.
[0063] Comparative Example 4
[0064] S1. At 70°C, add 1 part of nano-SiO2 to 15 parts of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, mix well to obtain a suspension, then add 1 part of sodium methoxide, stir under vacuum reflux at 100°C for 7 hours, and collect by filtration to obtain functionalized SiO2;
[0065] S2. Add HTPB, KH590 and functionalized SiO2 to the PET masterbatch, heat and melt to 230°C, stir at 150rpm for copolymerization for 2h, and then extrude and press into a PET film with a thickness of 15μm; the total amount of HTPB and KH590 is 4% of the amount of PET, and the amount ratio of HTPB to KH590 is 5:1; the amount of functionalized SiO2 is 2% of the amount of PET;
[0066] S3. Soak the iron plate in an ethanol solution and perform ultrasonic cleaning for 30 minutes to remove surface oil stains. After air drying, heat-compound the iron plate with a PET film at 230°C to obtain an iron-coated film.
[0067] The mechanical properties, intrinsic viscosity and oxygen barrier properties of the PET films prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were tested:
[0068] Mechanical properties: tested in accordance with DIN 53455;
[0069] Intrinsic viscosity ([η]): measured using an intrinsic viscosity meter at a temperature of (25±0.05)℃;
[0070] Oxygen barrier property: Use the differential pressure gas permeometer to test the oxygen permeability of a 15μm thick PET film. The temperature can be set by the instrument, the pressure is 0.1MPa, and the oxygen is high-purity oxygen.
[0071] The test results are shown in Table 1:
[0072] Table 1
[0073]
[0074] The coated iron prepared in Example 1 to Example 3 and Comparative Example 1 to Comparative Example 4 was tested for water resistance, acid resistance, salt resistance and peeling performance:
[0075] Water resistance: boil the sample in deionized water at 125℃ for 1h and observe the PET film shedding;
[0076] Acid resistance: Cook the sample in 3% acetic acid solution at 125℃ for 1h and observe the shedding of the PET film;
[0077] Salt resistance: Cook the sample in 3% salt solution at 125℃ for 1h and observe the PET film shedding;
[0078] Peel performance: refer to ASTM B 533-85 standard;
[0079] The above test results are shown in Table 2:
[0080] Table 2
[0081] Water resistant Acid resistant Salt tolerance Peelability Example 1 No shedding No shedding No shedding Unable to peel off, the body eventually breaks Example 2 No shedding No shedding No shedding Unable to peel off, the body eventually breaks Example 3 No shedding No shedding No shedding Unable to peel off, the body eventually breaks Comparative Example 1 A small amount of shedding A small amount of shedding A small amount of shedding Unable to peel off, the body eventually breaks Comparative Example 2 Partially fallen off Partially fallen off Partially fallen off Strippable Comparative Example 3 A lot of shedding A lot of shedding A lot of shedding Strippable Comparative Example 4 A small amount of shedding A small amount of shedding A small amount of shedding Strippable
[0082] As can be seen from Tables 1 and 2, the present invention prepares PET film by adding HTPB grafted silane and functionalized SiO2 to PET by co-extrusion. On the one hand, asymmetric monomers are introduced into the PET molecules to destroy the original structure and reduce the regularity of the molecular chain arrangement. HTPB grafted silane is used to introduce mercapto groups into PET, and the mercapto groups are used to adsorb with the iron plate to enhance the adhesion with the metal plate. On the other hand, the functionalized SiO2 is introduced to act as an oxidant in the copolymerization reaction and as a nucleating agent, and is loaded into the cross-linked structure network of PET. The prepared coated iron has excellent mechanical properties and gas barrier properties.
[0083] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0084] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing coated iron for packaging, characterized in that: The following steps are involved: S1. Add nano-SiO2 to methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate at 60-80°C, mix well to obtain a suspension, then add sodium methoxide, stir under vacuum reflux at 90-110°C for 6-8h, and collect by filtration to obtain functionalized SiO2; S2. HTPB and γ-mercaptopropyltrimethoxysilane were added to tetrahydrofuran, stirred and mixed, and then 2,2-dimethoxy-2-phenylacetophenone was added, and the mixture was reacted under 200W UV light for 2-4h, and the HTPB grafted silane was obtained by rotary evaporation; S3. Add HTPB grafted silane and functionalized Si O2 to PET, heat and melt to 220-240 ° C, stir the copolymerization reaction at a speed of 100-200 rpm for 1-3h, and then extrude and press into a PET film; S4. Thermally compounding the PET film with the pre-treated iron plate to obtain an iron-coated film.
2. The method for preparing the coated iron for packaging according to claim 1, characterized in that: The weight ratio of nano-SiO2, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)methyl propionate and sodium methoxide in S1 is 1:10-20:0.5-2.
3. The method for preparing the coated iron for packaging according to claim 1, characterized in that: The weight ratio of HTPB, γ-mercaptopropyltrimethoxysilane, tetrahydrofuran and 2,2-dimethoxy-2-phenylacetophenone in S2 is 1.5:0.3-0.4:50:0.
01.
4. The method for preparing the coated iron for packaging according to claim 1, characterized in that: The amount of HTPB grafted silane in S3 is 2-6% of the amount of PET.
5. The method for preparing the coated iron for packaging according to claim 1, characterized in that: The amount of functionalized SiO2 in the S3 is 1-3% of the amount of PET.
6. The method for preparing the coated iron for packaging according to claim 1, characterized in that: The thickness of the PET film in S3 is 10-20 μm.
7. The method for preparing the coated iron for packaging according to claim 1, characterized in that: The pretreatment of the iron plate in S4 is specifically to immerse the iron plate in an ethanol solution, perform ultrasonic cleaning for 10-30 minutes, and air-dry.
8. A film-coated iron for packaging, characterized in that: Prepared by any one of the preparation methods of claim 1 to claim 7.
